Produktivitas Budidaya Udang Vaname (Litopenaeus vannamei) Tambak Intensif di PT. Hasil Nusantara Mandiri Kelurahan Sungai Bulan Kecamatan Singkawang Utara - Suryadi, Suryadi; Merdekawati, Dewi; Januardy, Uray (Politeknik Negeri Sambas, 2021)
Shrimp that has the potential to be cultivated in ponds are giant tiger prawn (Penaeus monodon) and vaname shrimp (Litopenaeus vannamei). The advantages of this vaname shrimp are disease resistance, fast growth with a relatively short maintenance period of 100-110 days, high survival during maintenance, and low feed conversion value (FCR) (1:1,3). The objectives of the study were to evaluate the performance of vaname shrimp culture, identify problems and formulate intervention proposals in white vaname shrimp culture, and analyze income related to aquaculture productivity to determine the level of profit. The research was carried out in March-May 2021 at PT. Hasil Nusantara Mandiri, Sungai Bulan Village, North Singkawang District. This study uses a descriptive approach by observing productivity indicators, SR, FCR, and water quality as supporting data. Problem identification uses Root Cause Analysis and Fishbone Analysis. The results show that the productivity obtained is 24.233,48 kg, which is the company's target for 4 ponds, namely 48.000 kg. The income or profit is Rp. 106.199.842.